The Performance Measuring for Chinese Banking Industry During 2011-2018: Cost Efficiency and Profitability - Li, Yueyue (2019)
This dissertation was aimed to identify the cost efficiency and the determinants of profitability in Chinese banking industry over the period 2011-2018. To achieve the aim, Stochastic Frontier Analysis (SFA) and the System Generalized Method of Moments (SGMM) models were adopted. The research involved 105 Chinese commercial banks of different types, including state-owned commercial banks (SOCBs), joint-stock commercial banks (JSCBs), city commercial banks (CCBs), rural commercial banks (RCBs) and foreign commercial banks (FCBs). The research explored mediating influence of three variables, including ownership type, geographical regions and years, on cost efficiency. It was found that macroeconomic factors including the GDP growth rate (GDPGR), GDP per capita growth rate (GDPPCG), inflation rate (INF) and unemployment rate (UNE) had significant impact on Chinese banks’ cost efficiency. In addition, the CCBs were found to have the highest cost efficiency on average, whereas cost efficiency of the SOCBs was found to be the lowest. Moreover, the banks in eastern part of China were found to have the highest efficiency compared with their counterparts in the rest part of China. Furthermore, it was found that the deregulation of financial market (i.e. the interest rate marketization) improved the Chinese commercial banks’ efficiency. As for determinants of profitability, it was found that the profit of commercial Chinese banks was influenced by their previous performance and indicated that the banking sector in China was quite competitive. In addition, the results confirmed internal determinants of profitability, including size, liquidity, stability and efficiency. Moreover, macroeconomic determinants including GDP growth, inflation and unemployment rate all significantly influenced Chinese banks’ profitability. The research offered implications for further researchers and decision-makers.